Neurological disorders - convulsions after cardiac surgery in the pediatric population - Hristina Mandzukovska; R. Kacarska; A. Sofijanova; K. Maneva; V. Chadikovski; Lj. Kojik; Radica Muratovska-Delimitova; M. Kimovska-Hristova; S. Naunova-Timovska; T. Voinovska; S. Neshkova; B. Gjurkova; et al. (Medical Faculty, Ss. Cyril and Methodius University in Skopje, 2016)
Objectives Neurological disorders are complications that can occur after cardiac surgery of congenital heart defects. They manifest as seizures lasting from several seconds to several hours. For their confirmation, several diagnostic procedures are used, as well as a long-term monitoring of the clinical condition of the children. This is particularly important for a possible occurrence of subsequent neurological disorders that can occur few years later. Methods The clinical status and vital parameters of the operated children in the postoperative period are followed-up. If there are seizures manifested, diagnostic examinations are carried out, as well as EEG monitoring and anticonvulsant therapy is initiated. Results From 30 operated children, seizures appeared only in one child - 30/1 (33%) in the first 48 hours. The cause for its development is the intracranial bleeding during cardiac surgery and prolonged duration of 296 minutes of CPB and 60 minutes of X-cross time (aortic cross-clamping time). Hypothermia implemented during the CPB lasted 45 minutes and the temperature was 31C degrees. Due to the prolonged cardiac surgery and deterioration of general condition, the postoperative period was also prolonged. Conclusions The onset of seizures after cardiac surgery is a rare complication that occurs in the early postoperative period. They are the first marker of brain dysfunction which requires a long-term monitoring of the condition of these children, because there is an increased risk of dysfunctional and cognitive disturbances in the later period.
Keywords: neurological disorders; convulsions; CPB; hypothermia